Fractional Integral Inequalities of Hermite–Hadamard Type for Differentiable Generalized h-Convex Functions. (25th June 2020) - Yang, Yingxia; Saleem, Muhammad Shoaib; Ghafoor, Mamoona; Qureshi, Muhammad Imran
Abstract : In the present paper, some fractional integral inequalities of Hermite–Hadamard type for functions whose derivatives are generalized h -convex are established. Moreover, several particular cases are also discussed which can be deduced from our results. As special cases, one can obtain several new versions of the results of generalized h -convexity for other various generalizations of convex functions.